Cultivation Possibilities of Lemon Balm (Melissa officinalis L.) in the Central Anatolia Region of Turkey - Ahmet YENİKALAYCI; Mahmut GUNES; Kemal GUL (ISPEC Journal of Agricultural Sciences, 2021)
This study was carried out to determine yield and quality characteristics of Lemon balm (M. officinalis L.) in in 7 districts (7 locations) under Kayseri ecological conditions for 3 years in 2015-2017.  In this research, herbage yield, essential oil content, essential oil yield and components were determined. Dry herbage yields varied between 5250-6100 kg ha-1, essential oil contents varied between 0.07-0.24%, and essential oil yields as 4.2 lt ha-1. The main essential oil components were gereniol (1.90-20.77%), nerylacetate (1.13-34.63%), linalool (4.04-25.34%), neral (5.10-12.96%), caryophylleneoxide (0.78-15.17%), geranial (1.20-14.19%), β–caryophyllene (8.50-12.93%). In terms of herbage yield and essential oil quality, Yahyalı and Kocasinan districts, had favorable environmental conditions for lemon balm cultivation.